The role of endoscopic ultrasound on the preoperative T staging of gastric cancer: A retrospective study. Issue 36 (September 2016) - Han, Chaoqun; Lin, Rong; Shi, Huiying; Liu, Jun; Qian, Wei; Ding, Zhen; Hou, Xiaohua
Abstract : Abstract: Endoscopic ultrasonography (EUS) is used for preoperative assessment of gastric cancer. However, recent studies suggested that EUS staging accuracy is lower than previously thought. We aimed to assess EUS efficacy and image characteristics in preoperative gastric cancer T staging. A retrospective review of clinical and imaging features of 232 gastric carcinoma patients who underwent preoperative EUS assessment of T stage was performed. Only cases with tumor-free resection margin status and no metastases were enrolled. Comparisons of preoperative EUS and postoperative histopathological stagings were also performed to identify vital EUS image features for evaluating gastric carcinoma. EUS accuracy for T staging was 64.2% (149/232) with the highest accuracy for T3 (75.0%). Enlarged lymph nodes, well differentiated histological type and Borrmann IV type were associated with diagnostic accuracy in predicting tumor invasion. Although no factors were associated with overstaging, circumferential lesions ≥1/2, signet ring cell adenocarcinoma, and Borrmann IV type had significantly higher risks of understaging. Gastric wall outer edge irregularity was also an indicator of serosal involvement with a sensitivity of 82.0%. The pancreas and colon were more frequent disease extension sites than previously predicted. Although EUS is likely the best and most accurate option that we have used to stage gastric cancer, the finding that factors including circumferential lesions, signet ring cell adenocarcinoma, and Borrmann IV type carcinoma were more frequently related to incorrect staging warrants attention.